REAL ESTATE CHALLENGES UNDER CLIMATE change AND DEVELOPMENT CONSTRAINTS (Jurnal Spektran, 2026)
Climate change is reshaping the risk, return, and liquidity profile of real estate assets worldwide. Drawing on a structured narrative review, this article develops a Climate–Finance–Infrastructure (CFI) Interaction Framework to synthesize evidence on how physical climate risks and varying levels of economic development jointly affect real estate markets. The analysis focuses on three transmission channels—insurability, financing, and infrastructure—and compares their behavior across tropical versus temperate climates and developed versus developing economies. Existing evidence shows that rising exposure to heat, floods, and storms reduces insurance availability, raises premiums, and widens protection gaps; tightens credit conditions via higher lending margins, lower loan-to-value ratios, and shorter maturities; and places growing stress on protective and basic infrastructure systems. These pressures are systematically amplified in lower-income tropical settings, where weaker infrastructure, patchy maintenance, and limited public compensation mechanisms undermine resilience. In contrast, more mature markets can partly cushion impacts through adaptation investments, stricter building standards, and advanced risk-transfer instruments. The CFI framework highlights self-reinforcing feedbacks between these channels and identifies “climate-finance traps” in which climate exposure, infrastructure deficits, and risk-averse capital reinforce one another, particularly in tropical low- and middle-income economies. By mapping evidence into a four-quadrant typology (climate zone × development level) and illustrating it in several urban cases, the finding offers a diagnostic tool for investors, lenders, and policymakers to prioritize adaptation investments, redesign insurance and credit products, and align infrastructure and financial regulation with the realities of a warming climate
Keywords: Climate risk; markets; Insurance and Insurability